Splanchnic vein thrombosis in myeloproliferative neoplasms: pathophysiology and molecular mechanisms of disease. (March 2017) - How, Joan; Zhou, Amy; Oh, Stephen T.
Myeloproliferative neoplasms (MPNs) are the most common underlying prothrombotic disorder found in patients with splanchnic vein thrombosis (SVT). Clinical risk factors for MPN-associated SVTs include younger age, female sex, concomitant hypercoagulable disorders, and the JAK2 V617F mutation. These risk factors are distinct from those associated with arterial or deep venous thrombosis (DVT) in MPN patients, suggesting disparate disease mechanisms. The pathophysiology of SVT is thought to derive from local interactions between activated blood cells and the unique splanchnic endothelial environment. Other mutations commonly found in MPNs, including CALR and MPL, are rare in MPN-associated SVT. The purpose of this article is to review the clinical and molecular risk factors for MPN-associated SVT, with particular focus on the possible mechanisms of SVT formation in MPN patients.